Are stem cell characteristics altered by disease state? - Kicic, Anthony; Hall, C.M.; Shen, W.Y.; Rakoczy, P.E. (MARY ANN LIEBERT, INC, 2005)
Autologous stem cell transplantation combined with gene therapy can potentially be used to treat genetically inherited diseases. However, characterization of multipotential cells from a disease state remains extremely limited. We have characterized adult bone marrow stromal cells (MSCs) derived from three retinal degenerative mouse models and compared them to marrow stromal cells derived from their normal strain counterparts. Despite similar profiles soon after harvest, at 30 days post-isolation, marrow stromal cells derived from a disease origin were shown to contain a large pool (∼89-99%) of undifferentiated marrow stromal cells (CD90+/STRO-1+) as compared to their normal counterparts (∼19-43%). Fetal bovine serum appeared essential for marrow stromal cell proliferation and was not found to induce differentiation, although it could be substituted with other additives including epidermal growth factor (EGF), platelet-derived growth factor (PDGF), and leukemia inhibitory factor (LIF). We also showed that resulting CD90+/STRO+cells derived from both states could be directed into desired lineages expressing at the same rate and that they could be transduced with the same efficiency using different viral vehicles. This investigation has shown the existence of a large pool of undifferentiated stem cells derived from the disease state that have the potential to form the desired cell types when appropriately cued. © Mary Ann Liebert, Inc.